Design of Minimum Variance Controller for Strong Stabilization of Closed-loop Systems - Wang, Bangtao; Huang, Chunqing; Lan, Weiyao (Chinese Automation Congress (Online), 2023)
Strong stabilization of the closed-loop system is desirable for the practical application, in which the controller is required to be stable. In this paper, a design method of the minimum variance (MV) controller is proposed for strong stabilization of minimum phase and non-minimum phase systems subject to stochastic output disturbances. The effectiveness of the proposed design method is illustrated by the numerical example. It shows that the output variance of the proposed minimum variance controller is closed to that of the original (unstable) one.